2021
DOI: 10.1001/jamapediatrics.2021.0426
|View full text |Cite
|
Sign up to set email alerts
|

Association of Local Variation in Neighborhood Disadvantage in Metropolitan Areas With Youth Neurocognition and Brain Structure

Abstract: IMPORTANCE Neighborhood disadvantage is an important social determinant of health in childhood and adolescence. Less is known about the association of neighborhood disadvantage with youth neurocognition and brain structure, and particularly whether associations are similar across metropolitan areas and are attributed to local differences in disadvantage.OBJECTIVE To test whether neighborhood disadvantage is associated with youth neurocognitive performance and with global and regional measures of brain structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 136 publications
3
50
0
Order By: Relevance
“…Similarly, ABCD studies have demonstrated that low SES, and most specifically neighborhood disadvantage, is related to worse neurocognitive scores and reduced structural measures in frontal regions. Cortical deficits once again played a mediating role in the relationship between the other two variables [ 29 , 33 , 34 ]. Lastly, ABCD studies have shown that neighborhood disadvantage and individual measures of SES are associated with alterations in both task-based and resting-state functional connectivity related to reward anticipation and cognitive function [ 35 – 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ABCD studies have demonstrated that low SES, and most specifically neighborhood disadvantage, is related to worse neurocognitive scores and reduced structural measures in frontal regions. Cortical deficits once again played a mediating role in the relationship between the other two variables [ 29 , 33 , 34 ]. Lastly, ABCD studies have shown that neighborhood disadvantage and individual measures of SES are associated with alterations in both task-based and resting-state functional connectivity related to reward anticipation and cognitive function [ 35 – 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Association study Linear mixed-effects model (LMM) analyses were applied to identify the relationships between early RfP, brain structure, and a wide range of behavioural assessments, including cognition and psychiatric scores. The LMM model was recommended by the ABCD research consortium and has been used in several related studies (43)(44)(45) to consider the correlated observations within family structures due to siblings and twins and at different sites. In this study, LMM was performed using the fitlme function in MATLAB (R2019b, MathWorks), which was specialized to model families nested within sites.…”
Section: Discussionmentioning
confidence: 99%
“…Recent ABCD studies have provided proof-of-concept for brain-behavior-environment analyses that map neural parameters to multiple exposures 75, 76 , and for the potential to use a subset of environmental risk factors to explain variance in mental health outcomes 77 . In addition, several studies have reported associations of specific exposures with cognition and neuroimaging parameters in ABCD data (e.g., household income 42 , neighborhood disadvantage 78 , lead exposure 41 ). The studies mentioned above all used baseline ABCD data, which does not include key environmental exposures.…”
Section: Discussionmentioning
confidence: 99%